Electrocardiogram interpretation during nurse triage improves the performance of the triage system in patients with cardiovascular symptoms – A prospective observational study. (May 2023) - Zaboli, Arian; Ausserhofer, Dietmar; Sibilio, Serena; Toccolini, Elia; Paulmichl, Rupert; Giudiceandrea, Alberto; Bonora, Antonio; Pfeifer, Norbert; Turcato, Gianni
Highlights: Cardiovascular symptoms need an ECG for correct and complete evaluation. Trained nurses are able to correctly interpret ECGs in clinical practice. Triage improves its performance with the implementation of nurses' ECG interpretation. Abstract: Background: An immediate ECG on arrival of a patient with cardiovascular symptoms in the ED may anticipate the need for life-saving intervention. The aim was to evaluate whether ECG interpretation during nurse triage can improve triage system performance in patients with cardiovascular symptoms. Methods: All patients who required an assessment for cardiovascular symptoms were considered for this observational study. During triage assessment, the nurses assessed the patient's level of urgency applying the MTS, then again after this evaluation (confirming or modifying the level of urgency based on personal clinical experience) and after interpretation of the patient's ECG. The main study outcome was the diagnosis of an acute cardiovascular event. Results: Of the 1211 patients in the study, 10.5% presented the main study outcome. ECG interpretation in triage exhibited a nurse–physician agreement of 92.9% (p<0.001). increased patient priority in 7.5% of cases and reduced it in 39.6%. The discriminatory ability of the triage system had an area under the ROC of 0.712 and 0.845 after ECG interpretation. ECG interpretation improved the baseline assessment of priority, with an NRI of 60.1% (p<0.001). Conclusions: ECG interpretation in triage can be a simple and safe tool that improves the assessment of patient priority.